Factor Influencing Workers Safety In The Agricultural Sector - Ling, Lee Chiao (2001)
The research examines the factors that influencing workers safety in the Agricultural sector in Sabah and on Peninsular Malaysia. This study also further established the sensitivity of the management attitudes towards workers safety in the workplace. Besides, the safety locus of control scale was designed to predict the employees' accidents and injuries.